2009
DOI: 10.1182/blood-2009-03-211540
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-27 inhibition of HIV-1 involves an intermediate induction of type I interferon

Abstract: Infection of CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 51 publications
5
100
0
1
Order By: Relevance
“…2), an increased serum level of IL-32 might result in the acceleration of HIV-1 replication or spread in vivo. Recently, IL-27 has been shown to inhibit HIV-1 replication in macrophages (38,39). Interestingly, we found that M-CSF also significantly reduced the anti-HIV-1 activity of IL-27 (data not shown).…”
Section: Discussionmentioning
confidence: 61%
“…2), an increased serum level of IL-32 might result in the acceleration of HIV-1 replication or spread in vivo. Recently, IL-27 has been shown to inhibit HIV-1 replication in macrophages (38,39). Interestingly, we found that M-CSF also significantly reduced the anti-HIV-1 activity of IL-27 (data not shown).…”
Section: Discussionmentioning
confidence: 61%
“…Treatment of monocytes and T cells with IL‐27 induces BST‐2 in an IFN signaling‐independent manner 154. IL‐27 is a cytokine produced by myeloid cells 155 and functions to inhibit HIV‐1 replication in various cell types 156, 157, 158. Whether BST‐2 is one of the effectors of anti‐HIV‐1 activity of IL‐27 is yet to be determined.…”
Section: Bst‐2 Regulationmentioning
confidence: 99%
“…Our results showed that IL-27 represses the expression of HBV proteins and the replication of HBV capsid-associated DNA in HepG2.2.15, HepG2, and Huh7 cells in a dose-dependent fashion, suggesting that IL-27 plays an inhibitory role in HBV replication. IL-27 was reported to exhibit antiviral activity by inhibiting replication of HIV and HCV (12,13) and to produce IFN-inducible antiviral proteins by eliciting a type I IFN-like response (51,52), in which IFN-a initially binds to the type I IFN receptor, IFNAR1/2, and induces the phosphorylation of STAT1/2 and the expression of ISGs, which, in turn, initiate an antiviral state in target cells.…”
Section: Il-27 Enhances the Expression Of Ifn-l1 Receptors Il-28r1 Anmentioning
confidence: 99%
“…IL-27 is a heterodimeric anti-inflammatory cytokine composed of EBI3 and p28, which regulates Th cell function during autoimmune and pathogen-induced immune responses (1,3,4). IL-27 exhibits various therapeutic capabilities, such as regulating antiviral ability (12,13), enhancing antitumor immune responses (14), directing antiproliferative effects on tumors (15)(16)(17), and reducing the inflammation associated with experimental autoimmune arthritis (18,19). Serum IL-27 triggers an earlier immune response to prevent hepatic injury in different clinical-pathologic stages of HBV-infected patients (50).…”
Section: Il-27 Enhances the Expression Of Ifn-l1 Receptors Il-28r1 Anmentioning
confidence: 99%
See 1 more Smart Citation